Heterogeneous Effects of Missing out on a Place at a Preferred Secondary School in England - Emma Gorman; Ian Walker (Institute of Labor Economics (IZA), 2020)
Schools vary in quality, and high-performing schools tend to be oversubscribed: there are more applicants than places available. In this paper, we use nationally representative cohort data linked to administrative education records to study the consequences of failing to gain admission to oneâ exteuro™s first-choice secondary school in England. Our empirical strategy leverages features of the institutional setting and the literature on school choice to make a case for a selection-on-observables identifying assumption. Failing to gain a place at a preferred school had null to small impacts on short-run academic attainment, but was associated with large reductions in mental health and increased fertility in early in adulthood. These effects are especially pronounced in areas which deployed a manipulable assignment mechanism to allocate school places, where we detected larger detrimental effects on high-stakes examination outcomes. A potential channel is increased early engagement in risky behaviours. Our results show that schools are important in shaping more than test scores, and that the workings of the school admission system play a fundamental role in ensuring access to good schools.
Keywords: I21; I24; J24; H44; D47; 330; risky behaviours; market design; human capital; school choice; education